Enhancement of aerodynamic performance of H-Darrieus rotor using wraparound fairing system: A 2D CFD study - Boulla, Douha; Fertahi, Saif ed-din; Bernatchou, Maryam; Samaouali, Abderrahim; Ajani, Meryeme; boussaq, Chaimae (International Journal of Renewable Energy Development, 2025)
The aim of this article is to improve the aerodynamic performance of a three-bladed vertical axis H-Darrieus wind turbine, which is equipped with different types of fairings. To this end, a 2D CFD simulation combined with calculations based on the resolution of the Steady Reynolds-Averaged Navier-Stokes equations (RANS) and the SST  turbulence model was used. In addition, the multiple reference frame (MRF) method was applied for the simulation. The simulation results show that the power coefficient () reaches maximum values equal to 0.561, 0.580 and 0.607 for the NACA2412, Eppler 423 and DAE-11 profiles respectively, for a chord length C = 3 and a tip speed ratio (TSR) equal to 2.5. Then, the torque coefficient () reaches the highest value of  = 0.354 at  = 20° for the DAE-11 fairing, which means that this profile performs better, particularly at higher angles of attack. These results confirm that the DAE-11 fairing surpassed the Eppler 423 and NACA2412 profiles. Unstable vortex field formation has been observed between the turbine and the fairing, at the leading and trailing edges, for both low and high fairing chord lengths. This phenomenon can increase torque and disrupt flow direction at low velocity. On the other hand, when the chord length reaches a medium value, a more stable flow zone appears. It can therefore be concluded that the addition of a fairing to the H-Darrieus rotor with a suitable chord length improves the turbine aerodynamic performance, particularly in terms of flow stabilization and reduction of the stagnation zone.